Introduction to homeland security - Bullock, Jane A. (Butterworth-Heinemann, 2006)
Completely revised and updated new edition of best-selling text complete with full color throughout!
Keywords: Terrorism -- Prevention -- Government policy -- United States.; National security -- United States.; Civil defense -- United States.; Emergency management -- United States.; Terrorisme -- Prévention -- Politique gouvernementale -- États-Unis.; POLITICAL SCIENCE -- Political Freedom & Security -- Law Enforcement.; Civil defense; Emergency management; National security; Terrorism -- Prevention -- Government policy; United States; dissertations.; Academic theses; Academic theses.; Thèses et écrits académiques.